2014
DOI: 10.1103/physreva.90.012338
|View full text |Cite
|
Sign up to set email alerts
|

Average entanglement dynamics in open two-qubit systems with continuous monitoring

Abstract: We present a comprehensive implementation of the quantum trajectory theory for the description of the entanglement dynamics in a Markovian open quantum system made of two qubits. We introduce the average concurrence to characterize the entanglement in the system and derive a deterministic evolution equation for it that depends on the ways information is read from the environment. This builded in flexibility of the method is used to address two actual issues in quantum information: entanglement protection and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Remarkably, we are able to construct explicitly a measurement on a realistic quantum environment that realizes an environment-assisted entanglement protection scenario, generalizing earlier considerations on Markov open quantum systems [22,46,47].…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…Remarkably, we are able to construct explicitly a measurement on a realistic quantum environment that realizes an environment-assisted entanglement protection scenario, generalizing earlier considerations on Markov open quantum systems [22,46,47].…”
mentioning
confidence: 84%
“…Exact results on entanglement evolution in multipartite open systems with non-Markovian dynamics are scarce [9], making it difficult to asses how tight our bound really is. Yet, for the case of two qubits with only one of them coupled to a dephasing channel, the exact entanglement dynamics is given in [22] for Markovian and in [44] for non-Markovian dynamics, our bound exactly reproduces this entanglement evolution. Indeed, our bound is also exact for any N -partite open system, where only one subsystem of dimension two is exposed to an arbitrary dephasing channel [37].…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…For weak fields the unraveling is irrelevant, as the system is well approximated by a pure state for many lifetimes, as the jump rate P (t)dt = γ σ z (t) + 1/2 dt and σ z (t) ≈ −1 for weak fields, so jump events are relatively rare. It has been shown that while entanglement is different for different unravelings, for a given unraveling all measures of entanglement show similar behavior as system parameters are changed [16].…”
Section: Introductionmentioning
confidence: 99%